Employee wellbeing : contemporary workplace challenges and evidence-based interventions - Vishwanathan, Pooja (Routledge, 2025)
"Drawing on work and positive psychology, this insightful book addresses contemporary workplace challenges and analyses evidence-based interventions in the employee wellbeing domain"--